2022
DOI: 10.1177/01945998211073707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biologic Characteristics and Outcomes in Young and Middle‐Aged Patients With Laryngeal Cancer: A Retrospective Cohort Analysis

Abstract: Objective To describe the clinical and biologic characteristics and outcomes of young and middle-aged (YMA; <65 years) patients according to the presence or absence of traditional risk factors for laryngeal cancer. Study Design Retrospective cohort analysis. Setting Single-institution academic medical center. Methods Patients without a history of clinically significant tobacco use or heavy alcohol use were defined as “nontraditional”: ≤5 pack-years, ≤5 years smoked, ≤14 alcoholic drinks per week, and ≥15-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A handful of other investigators have also highlighted the unique patient‐ and tumor‐level characteristics of younger patients with laryngeal cancer and wondered if these findings pointed to a nontraditional disease etiology 9,14,17,18 . A recent study of young patients with laryngeal cancer (<40 years old) has similarly shown that young patients are more likely to be female compared to older patients (33.6% vs. 19.6%) 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A handful of other investigators have also highlighted the unique patient‐ and tumor‐level characteristics of younger patients with laryngeal cancer and wondered if these findings pointed to a nontraditional disease etiology 9,14,17,18 . A recent study of young patients with laryngeal cancer (<40 years old) has similarly shown that young patients are more likely to be female compared to older patients (33.6% vs. 19.6%) 9 .…”
Section: Discussionmentioning
confidence: 99%
“…A SEER national database study reported that younger cohorts, when compared to their older counterparts, contained a higher proportion of female patients, had more cases of glottic involvement, and were less likely to seen with distant metastatic disease 9 . In addition, a handful of studies have reported heterogeneous survival outcomes 9–14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation